FOOD LITERACY AS A COMPONENT OF A PERSON’S ECONOMIC SECURITY - Sausheva, Oksana; Lizina, Olga; Ilyakova, Irina; Fedonina, Oksana (Revista Inclusiones, 2020)
The study relevance is triggered by the need for the food formation literacy of the population as one of the main economic security conditions of an individual, which is especially relevant in modern conditions of increasing social and demographic threats. The purpose of the article is to study Russian and European practices in food literacy formation of the population, in order to develop recommendations for its improvement and testing. The leading method is the systematic or integrative method, which requires the analysis of economic, legal, medical and other prerequisites for the comprehensive competencies formation of students in the field of food literacy. As a result, it could be concluded that modern educational programs should meet the current trends, among which the vital one is healthy lifestyle and proper nutrition. Practical relevance lies in the possibility of using the training modules and programs to increase food literacy in higher educational institutions; in addition, the results of the study may be useful both to education specialists in the field and general public.